The Comparison of The Moral Values in Snow White and The Seven Dwarfs by Vera Southgate Version and Snow White and The Seven Dwarfs by Regis Maine Version Using The Pragmatic Approach - Saraswati, Ni Putu Ika (Jurnal Penelitian Mahasiswa Indonesia, 2022)
This study aims to determine the comparison of the moral values in Snow White and The Seven Dwarfs by Vera Southgate version and snow white and the seven dwarfs by Regis Maine version using the pragmatic approach. This research is basic qualitative research. this research used a pragmatic approach in analyzing the moral values of the story snow white and seven dwarfs by Vera Southgate and by Regis Maine. Data in the form of words, phrases, sentences, or fragments from the first chapter to the last chapter. The result of this study is a comparison of moral values in the snow-white story that appears in snow white and the seven dwarfs by Vera Southgate Version and Snow White and The Seven Dwarfs by Regis Maine Version. The two books tell about Snow White and The Seven Dwarfs but with different moral values.